A study on awareness of intellectual freedom among IIUM Library community - Diallo, Souleymane; Abu Bakar, Ahmad Bakeri (IIUM Press, 2011)
The purpose of this study is to highlight the importance of intellectual freedom in academic libraries. The librarians who provide services to the users should exercise equal access and opportunity to match the needs of the user. The librarians should refrain from taking a particular position that can be construed by others to be associating with some form of biasness related to the contents of the library materials. On the other hand, users should also be aware of the provisions of the intellectual freedom so that they can exercise their rights when they find their rights are being threatened by those decision makers in the academic libraries. They could make their voices heard by those in the academic libraries by filing complains informal or formal to the academic libraries management. This complains could be the result of certain controversial publications which are being censored by the academic library uthorities. The academic libraries could confront these problems by roping their allies such as the press and other media to help them in giving a fairer deal of the actual situation.